Beyond virtual and augmented reality: AI-assisted mixed reality and its impacts on society - Japutra, A.; Bilro, R.G.; Loureiro, S. M. C. (Managerial challenges and social impacts of virtual and augmented reality, 2020)
The chapter presents how Artificial Intelligence (AI) is combining with Virtual Reality and Augmented Reality. The evolution of AI is discussed, as well as its consequences. The chapter also provides an overview of the four types of intelligence in AI, and provides positive and negative impacts for society. The discussion on positive and negative effects of AI brings to light how it can help humans, but at the same time, how it can also transform society and firms. The rise of hybrid humans may be a turning point to develop a new global order, with new laws, justice, rights, and duties.